2017
DOI: 10.1016/j.marchem.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of dissolved CO2 with cadmium isotopes in the Southern Ocean

Abstract: A B S T R A C THere we report the first ever observations of a strong correlation in ocean surface waters of the dissolved δ 114 Cd with dissolved CO 2 . This is observed in the Southern Ocean along the 0°W meridian in both and its conversion to CO 2 . For this the algae need more enzyme carbonic anhydrase that normally has Zn as its co-factor, but Cd may substitute for Zn and there also are Cd-specific carbonic anhydrases known for some phytoplankton species. Indeed in incubations of the local plankton commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…2016, de Baar et al . 2017). Adsorption and precipitation also produce measurable Cd isotope fractionation (Horner et al .…”
mentioning
confidence: 99%
“…2016, de Baar et al . 2017). Adsorption and precipitation also produce measurable Cd isotope fractionation (Horner et al .…”
mentioning
confidence: 99%
“…Surface waters of the Antarctic Ocean comprise ample major nutrients. Quite remarkably dissolved ''nutrient-type" trace metals Zn, Cd, Ni and Cu show the same trend with higher concentrations in Antarctic surface waters (de Baar et al, 2017c; their Table 1). Notably dissolved Zn and Cd are much higher in Antarctic surface waters than in the surface waters of the oligotrophic central North Pacific Ocean, but Ni and Cu are elevated as well when compared with the central North Pacific.…”
Section: Preceding Observations Of Zn CD Ni Cu and Nutrientsmentioning
confidence: 79%
“…The Antarctic Ocean shows elevated REE in surface waters, following the trend of elevated major nutrients and trace metals (de Baar et al, 2017c, their Hathorne et al (2015) are all situated south of the APF and in the upper 1000 m of the water column show significantly higher REE concentrations than in the upper 1000 m of their stations 101 and 104 situated north of the APF. Because of these 'High Nutrient' conditions in upper waters of the Antarctic Ocean, the Antarctic relationships of the trivalent REE with the major nutrients are not necessarily suitable for comparison with the extremely oligotrophic (nutrient-depleted) conditions in upper waters of the central North Pacific Ocean.…”
Section: Prior Observations Of Ree and Major Nutrients In The World Oceansmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, the distributions of dissolved Cd and Zn, as well as their isotopic ratios in the global ocean, are profoundly influenced by the biological uptake of these metals in surface waters (Conway and John 2015; Vance et al 2017; Zhang et al 2019). For example, de Baar et al (2017) observed strong correlations between δ 114 Cd and dissolved concentrations of Cd and CO 2 in the surface waters of the Southern Ocean, all of which can be directly linked to biological uptake.…”
mentioning
confidence: 99%